Collection times and volumes of INP samples from Antarctica, Princess Elisabeth station and west of and on the northern Antarctic Peninsula - Eckermann, Oliver; Mangold, Alexander; Van Overmeiren, P; Zeppenfeld, Sebastian; van Pinxteren, Manuela; Dall'Osto, Manuel; Henning, Silvia; Wex, Heike (In: Eckermann, O et al. (2025): INP data from Antarctica, Princess Elisabeth station and west of and on the northern Antarctic Peninsula [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974235, 2025)
Ice nucleating particles (INPs) are important atmospheric particles influencing the formation of ice in clouds. Their sources and atmospheric concentrations currently are subject of plenty of research. The here provided data on INPs (Ice Nucleating Particles) were derived from particles collected onto filters for two separate projects: 1) Sampling during two austral summers 2020/2021 and 2021/2022, for the CLIMB project (How do aerosol-CLoud Interactions influence the surface Mass Balance in East Antarctica?) at the Belgian Princess Elisabeth station (PES), a zero emission station, installed on a mountain ridge of Utsteinen Nunatak. 2) Sampling during a field campaign during PI-ICE (Polar atmosphere ice-ocean Interactions: Impact on Climate and Ecology) west of and on the northern Antarctic Peninsula in January until March 2019. Filters were analyzed at the TROPOS ice-lab in Germany, using well established off-line techniques. Detailed information on sampling and data evaluation are given in the abovementioned publication which this data-set accompanies. Measured frozen fractions are provided for samples, field blinds and heated samples, INP concentrations are provided for samples both with and without subtracting the background.
Keywords: Antarctica; Antarctic Peninsula; ice nucleating particles (INP); Princess Elisabeth Station